Current directions in tau research: Highlights from Tau 2020. Issue 5 (28th September 2021) - Sexton, Claire; Snyder, Heather; Beher, Dirk; Boxer, Adam L.; Brannelly, Pat; Brion, Jean‐Pierre; Buée, Luc; Cacace, Angela M.; Chételat, Gaël; Citron, Martin; DeVos, Sarah L.; Diaz, Kristophe; et al.
Abstract: Studies supporting a strong association between tau deposition and neuronal loss, neurodegeneration, and cognitive decline have heightened the allure of tau and tau‐related mechanisms as therapeutic targets. In February 2020, leading tau experts from around the world convened for the first‐ever Tau2020 Global Conference in Washington, DC, co‐organized and cosponsored by the Rainwater Charitable Foundation, the Alzheimer's Association, and CurePSP. Representing academia, industry, government, and the philanthropic sector, presenters and attendees discussed recent advances and current directions in tau research. The meeting provided a unique opportunity to move tau research forward by fostering global partnerships among academia, industry, and other stakeholders and by providing support for new drug discovery programs, groundbreaking research, and emerging tau researchers. The meeting also provided an opportunity for experts to present critical research‐advancing tools and insights that are now rapidly accelerating the pace of tau research.